Electromyography analysis for assessment of lower extremity muscles during squat and stoop movement / Nurul Atma Athirah Ahmad Azali ... [et al.] - Ahmad Azali, Nurul Atma Athirah; Che Zakaria, Noor Ayuni; Mohd Mustafah, Nadia; Othman, Nurul Atiqah; Abdul Latip, Eli Nadia; Azaman, Aizreena (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
There are diverse styles of lifting an object from the ground and each style employs different types of muscles with varying degrees of usage. The objective of this study was to explore the muscle activities between squat and stoop movement while lifting the load in to understand risk of low back pain and muscles fatigue. The muscles involved in this study are medial head of gastrocnemius, quadriceps femoris and erector spinae. Electromyography (EMG) analysis comparing the stoop and squat technique were systematically reviewed. The selected subjects were two healthy males and two healthy females with same body mass index (BMI) range (18.5 - 24.9). ProEMG stand-alone V2.1.2.5 software was used to analyse the activities of the muscles. The subjects performed 15 repetition of stooping and squatting as recommendation by SENIAM. We found that squat load lifting is safer and cause less muscle fatigue compared to stoop load lifting.